2021
DOI: 10.1038/s41598-021-83637-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of SLA-DRB1 genetic diversity in Colombian (creoles and commercial line) and worldwide swine populations

Abstract: Analysing pig class II mayor histocompatibility complex (MHC) molecules is mainly related to antigen presentation. Identifying frequently-occurring alleles in pig populations is an important aspect to be considered when developing peptide-based vaccines. Colombian creole pig populations have had to adapt to local conditions since entering Colombia; a recent census has shown low amounts of pigs which is why they are considered protected by the Colombian government. Commercial hybrids are more attractive regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Therefore, the genetic characteristics of the two protein families are similar. For swine leukocyte antigen (SLA) genes, which is the MHC genes of pig, it has been well documented that the presence of an extremely large number of alleles, a large difference in allelic constitution among different breeds, and breed-speci c alleles [42][43][44][45][46][47] are most likely to result from independent breeding histories for different breeds. In addition, the characteristics of pig OR genes analyzed in this current study showed similarities to those of the SLA genes described above.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the genetic characteristics of the two protein families are similar. For swine leukocyte antigen (SLA) genes, which is the MHC genes of pig, it has been well documented that the presence of an extremely large number of alleles, a large difference in allelic constitution among different breeds, and breed-speci c alleles [42][43][44][45][46][47] are most likely to result from independent breeding histories for different breeds. In addition, the characteristics of pig OR genes analyzed in this current study showed similarities to those of the SLA genes described above.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the genetic characteristics of the two protein families are similar. For swine leukocyte antigen ( SLA ) genes, which is the MHC genes of pig, it has been well documented that the presence of an extremely large number of alleles, a large difference in allelic constitution among different breeds, and breed-specific alleles 44 49 are most likely to result from independent breeding histories for different breeds. In addition, the characteristics of pig OR genes analyzed in this current study showed similarities to those of the SLA genes described above.…”
Section: Discussionmentioning
confidence: 99%
“…The group of MHC-related genes encodes an extensive repertoire of surface proteins playing a crucial role in recognising mammalian antigens; in spite of large differences between species, their variability has been associated with susceptibility to or protection against infectious diseases and even cancer [49,50]. Most research regarding class II molecules has focused on the DRB1 locus (DRB3 in cattle) as being the most variable and having the greatest cell-related expression; on the contrary, DRA is considered practically invariant [50][51][52][53]. Manczinger et al (2019) proposed that human DRB1 MHC-II allele response could be categorised into two groups; specialists (alleles able to bind to a few epitopes) and generalists (providing protection against a broad range of pathogens).…”
Section: Genetic Variability and Immune Responsementioning
confidence: 99%
“…Regarding veterinary studies, a study has explored the MHC in different species. Allele frequency and diversity in pigs has been analysed in wild and production species which are of interest, due to their biological characteristics, their use in biomedical studies, transplants, regenerative medicine, and vaccine design [53,55,56]. Hammer et al (2021), for example, used low-resolution (Lr) SLA haplotyping for characterising European SLA-I (SLA-1, SLA-2, and SLA-3) and SLA-II genes (DRB1, DQB1, DQA) in 549 pigs representing nine commercial lines from various production systems; they identified 50 class I haplotypes and 37 class II ones.…”
Section: Genetic Variability and Immune Responsementioning
confidence: 99%